Aplikasi Nanocoating Berbasis Pektin dan Nanopartikel ZnO untuk Mempertahankan Kesegaran Salak Pondoh - Iman Sabarisman; Nugraha Edhi Suyatma; Usman Ahmad; Fahim Muchammad Taqi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Snake fruit (Salacca edulis Reinw.) is one of the leading agricultural commodities in Indonesia with sweet taste and crispy texture. Unfortunately, it has a short storage life due to high respiration and transpiration and fungal decay. Therefore, the present study was aimed to evaluate the effect of pectin-based nanocomposite coating on postharvest quality of snake fruit stored at ambient temperature. The pectin solution was prepared by dispersing ZnO NPs (2%, w/w to pectin) and stearic acid (1%, w/w to pectin) into a pectin solution (1%, w/v in distilled water). Snake fruits were coated by dipping method and stored at room temperature during 14 days. The quality parameters and microbial growth were evaluated periodically. Results showed that application of nanocomposite coating on snake fruit could reduce weight loss (from 41.18±1.77% to 27.78±1.20%) and inhibit microbial growth (from 7.52 log cfu/g to 4.48 log cfu/g) significantly. The coating layer was transparent so did not affect the appearance of snake fruit. Thus, these results suggest that the pectin-based nanocomposite coating might provide an alternative method to maintain storage quality of snake fruit.